Control strategy for islanded DC microgrids - Zhang, Shilong (Nanyang Technological University, 2025)
DC microgrid is an important means to realize distributed power energy supply in the future, and is an important part of the future power system. However, due to the instability of clean energy itself and the occasional communication delay or even failure, and other unstable factors between the system will bring many impacts on the daily supply of the power grid. How to solve these problems to achieve the two control goals of bus voltage regulation and current sharing among degeneration units has aroused the research interest of many scholars. In this dissertation, a master-slave control strategy of islanded DC microgrid is adopted. A small AC signal carrying current information is transmitted in the power system to realize voltage regulation and current sharing between different DGUs. This approach enables accurate current sharing without communication, and inhibits the impact of related variations and disturbances on voltage regulation performance. The designed experiments verify the feasibility of the proposed method from the perspectives of validity verification, load switching and voltage variation.